Testicular toxicity and sperm quality following cadmium exposure in rats: Ameliorative potentials of Allium cepa - Serah F Ige; Samuel B Olaleye; Roland E Akhigbe; Titilayo A Akanbi; Olanrewaju A Oyekunle; Utibe-Abasi S Udoh (Wolters Kluwer Medknow Publications, 2012)
Aims: This study was carried out to investigate the effect of Allium cepa crude extract on cadmium-induced testicular toxicity in rats. Materials and Methods: Adult male Sprague-Dawley rats were randomized into 4 groups (n = 6). Group 1 was used as control, group 2 was administered 0.3 mg/kgBW of cadmium sulfate (CdSO 4 ) intraperitoneally for 3 days, group 3 was pretreated with 1 ml/100 g BW of Allium cepa (AcE) for 8 weeks followed by intraperitoneal administration of 0.3 mg/kgBW of CdSO 4 in the last 3 days of experiment, and group 4 was administered 1 ml/100 g BW of AcE throughout the experiment. Testicular weight and semen analysis revealing the sperm count, sperm motility, and sperm morphology was carried out. Superoxide dismutase (SOD), catalase activities, and lipid peroxidation status were also carried out in testes. Results: The study demonstrated that Allium cepa ameliorated CdSO 4 -induced alteration in testicular weight, sperm count, sperm motility, and sperm morphology. It also showed that Allium cepa attenuated the derangement of lipid peroxidation profile in testicular tissues caused by CdSO 4 exposure. Conclusions: The findings in the study showed that pre-treatment of rat model with Allium cepa extract prevented CdSO 4 -induced reproductive toxicity by improving sperm quality and enhancing testicular lipid peroxidation status.